Interpreting Variants of Uncertain Significance in PCD: Abnormal Splicing Caused by a Missense Variant of DNAAF3 - Haixia Zheng; Chongsheng Cheng; Miao He; Wangji Zhou; Yixuan Li; Jinrong Dai; Ting Zhang; Kai‐Feng Xu; Xue Zhang; Xinlun Tian; Yaping Liu (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Primary ciliary dyskinesia (PCD) is a rare autosomal recessive disorder characterized by dysfunction of motile cilia. While approximately 50 genes have been identified, around 25% of PCD patients remain genetically unexplained; elucidating the pathogenicity of specific variants remains a challenge. Methods Whole exome sequencing (WES) and Sanger sequencing were conducted to identify potential pathogenic variants of PCD. Minigene assays were performed to evaluate the pathogenicity of variants. Transmission electron microscopy (TEM) and high‐speed video analysis (HSVA) were conducted to analyze the function of cilia in respiratory epithelial cells. Results We identified two variants of DNAAF3: c.557G>A, p.G186E in exon 5, and c.1364G>A, p.G455D at the terminal nucleotide of exon 10 in a 16‐year‐old male patient. Through a minigene assay, we demonstrated that the c.1364G>A variant led to a four‐nucleotide skipping. The cilia in epithelial ciliary cells of the proband were almost immotile. The absence of outer dynein arms and inner dynein arms was also observed. Conclusions Our study identified two compound heterozygous variants of DNAAF3, a pathogenic gene for PCD, and proved that a novel missense variant c.1364G>A affects splicing. Our findings not only expanded the spectrum of mutations in the DNAAF3 gene but also highlighted the importance of investigating variants of uncertain significance (VUS) for comprehensive genetic diagnoses.